Colonization by Streptococcus agalactiae during pregnancy: maternal and perinatal prognosis - El Beitune,Patrícia (2005)
We reviewed colonization by group B Streptococcus beta-haemolyticus of Lancefield (SGB), or Streptococcus agalactiae, in pregnant women, and the consequences of infection for the mother and newborn infant, including factors that influence the risk for anogenital colonization by SGB. We also examined the methods for diagnosis and prophylaxis of SGB to prevent early-onset invasive neonatal bacterial disease. At present, it is justifiable to adopt anal and vaginal SGB culture as part of differentiated obstetrical care in order to reduce early neonatal infection. The rates, risk factors of maternal and neonatal SGB colonization, as well as the incidence of neonatal disease, may vary in different communities and need to be thoroughly evaluated in each country to allow the most appropriate preventive strategy to be selected.